Pulsed laser deposited GeTe-rich GeTe-Sb(2)Te(3) thin films - Bouška, M. (Sci Rep, 2016)
Pulsed laser deposition technique was used for the fabrication of Ge-Te rich GeTe-Sb(2)Te(3) (Ge(6)Sb(2)Te(9), Ge(8)Sb(2)Te(11), Ge(10)Sb(2)Te(13), and Ge(12)Sb(2)Te(15)) amorphous thin films. To evaluate the influence of GeTe content in the deposited films on physico-chemical properties of the GST materials, scanning electron microscopy with energy-dispersive X-ray analysis, X-ray diffraction and reflectometry, atomic force microscopy, Raman scattering spectroscopy, optical reflectivity, and sheet resistance temperature dependences as well as variable angle spectroscopic ellipsometry measurements were used to characterize as-deposited (amorphous) and annealed (crystalline) layers. Upon crystallization, optical functions and electrical resistance of the films change drastically, leading to large optical and electrical contrast between amorphous and crystalline phases. Large changes of optical/electrical properties are accompanied by the variations of thickness, density, and roughness of the films due to crystallization. Reflectivity contrast as high as ~0.21 at 405 nm was calculated for Ge(8)Sb(2)Te(11), Ge(10)Sb(2)Te(13), and Ge(12)Sb(2)Te(15) layers.